Castoriadis, Veblen and the 'Power Theory of Capital' - David Troy Cochrane (Depoliticization: The Political Imaginary of Global Capitalism, 2011)
A critical examination of value theories, capital accumulation and organized power.
Keywords: 330; capital; capitalization; differential accumulation; labour value